Pembuatan Game Pembelajaran Interaktif Mengenai Hewan Berbasis Android : Studi Kasus RA Darul Ulum Sarirogo - Mulyo, Budi Mukhamad; Fahrial, Rifki Zainal; Putradira, Muhammad Rizki (INTECH (Informatika dan Teknologi), 2024)
Early childhood education is crucial for children's cognitive development. In the digital era, utilizing Android-based technology, such as games, can enhance the learning experience. This study aims to develop an interactive learning game, Joynimal, to introduce animals to children aged 4-7 years at RA Darul Ulum Sarirogo. Using Unity 2D, this game is designed to facilitate animal learning with an interactive and enjoyable approach. The research methodology includes literature study, needs analysis and design, implementation, testing, and game release. The questionnaire results from 30 respondents show that 66.03% strongly agree that this game is effective in improving children's cognitive abilities. The aspects of appearance, the aspects of difficulty, the aspects of game system, the aspects of and educational delivery also received very positive responses with percentages of 68.58%, 59.50%, 67.95%, and 67.41%, respectively. This study concludes that Joynimal is effective as an interactive learning tool that is engaging and beneficial for early childhood education, helping to enhance cognitive skills, shape recognition, and vocabulary in a fun way, as well as motivating children to learn in a more engaging and interactive manner.